Acute Necrotizing Pancreatitis Associated with Vildagliptin - Kunjathaya, Purnima; Ramaswami, Pradeep Kakkadasam; Krishnamurthy, Anupama Nagar; Bhat, Naresh (JOP. Journal of the Pancreas, 2013)
Context To report a case of acute necrotizing pancreatitis in a patient receiving vildagliptin. Case report A 49-year-old man presented to us with severe abdominal pain and was diagnosed to have pancreatitis three weeks after the commencement of vildagliptin for the treatment of uncontrolled type 2 diabetes mellitus. His serum amylase was 2,215 U/L at admission, with contrast enhanced computed tomography (CECT) of the abdomen and pelvis showing features of acute pancreatitis. The patient had a prolonged hospital course and underwent laparoscopic pancreatic necrosectomy to relieve him of his biliary obstruction and an endoscopic retrograde cholangiopancreatography (ERCP) and biliary stenting as he had an avulsion of the cystic duct during surgery. Conclusions Acute pancreatitis as a complication of other incretin-based therapy like sitagliptin and exenatide is known and well reported, and has prompted the US Food and Drug Administration to issue an alert on these drugs. This appears to be the first reported case of acute necrotizing pancreatitis in a patient receiving vildagliptin in India and reinforces the need to be more judicious in the use of this medication. Image: MRI abdomen showing pancreatic necrosis compressing on the common bile duct.